Advances in visual computing : 13th International Symposium, ISVC 2018, Las Vegas, NV, USA, November 19-21, 2018, Proceedings /: 13th International Symposium, ISVC 2018, Las Vegas, NV, USA, November 19-21, 2018, Proceedings. (2018) - Unknown
No abstract available